The Philosophy of Rhetoric, Volume 2 - Campbell, George 1719-1796 (Cambridge library collection. Philosophy, 1776)
A leading figure of the Scottish Enlightenment, George Campbell (1719–96) began to write what was to become his most famous work, The Philosophy of Rhetoric, soon after his ordination as a minister in 1748. Later, as a founder of the Aberdeen Philosophical Society, he was able to present his theories, and these discourses were eventually published in 1776. In the spirit of the Enlightenment, Campbell combined classical rhetorical theory with the latest thinking in the social, behavioural and natural sciences. A proponent of 'common sense' philosophy, he was particularly interested in the effect of successful rhetoric upon the mind. Published in two volumes, the work is divided into three books. Volume 2 contains the concluding part of Book 2 and all of Book 3, which shows the author at his most intricate, expanding upon the correct selection, number and arrangement of words required for successful argument